2020
DOI: 10.2174/1874104502014010035
|View full text |Cite
|
Sign up to set email alerts
|

Anethum graveolens L‎. Alleviates Sperm ‎Damage by Limiting Oxidative Stress ‎and Insulin ‎Resistance ‎in ‎Diabetic Rats ‎

Abstract: Background: It has been reported that diabetes is associated with sperm ‎damage and infertility. Objective: The purpose of this experiment was to survey the effect of Anethum graveolens L. (Dill) powder on sperm profiles, oxidative stress, insulin resistance, and histological changes in male diabetic rats. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The minimum number of animals was used, safety procedures were compiled in all mandatory experimental works, and minimum suffering of animals was considered in all experiments. The concentration of dill tablet (300 mg/kg) which was used in the present study was based on the previously described optimal concentration [ 13 , 18 ]. Other report indicated that the 300 mg/kg dill hydroalcoholic extract is effective dose [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum number of animals was used, safety procedures were compiled in all mandatory experimental works, and minimum suffering of animals was considered in all experiments. The concentration of dill tablet (300 mg/kg) which was used in the present study was based on the previously described optimal concentration [ 13 , 18 ]. Other report indicated that the 300 mg/kg dill hydroalcoholic extract is effective dose [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anethum graveolens (dill) is one of the traditional herbal plant with many useful effects [ 10 , 11 ]. Dill is recognized as a rich source of phenolic, flavonoids, saponin, cardiac glycosides and terepene [ 12 , 13 ]. These components have potential antioxidant and hypolipidemic effects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings propose that appropriate supplementation of these vitamins may increase our resistance to COVID-19 infection. Antioxidant supplementation is potentially recommended in COVID-19 patients with primary underlying diseases, such as hypertension, diabetes, coronary heart disease, and cancer [ 7 , [45] , [46] , [47] ].…”
Section: Control and Treatment Of Hyperglycemia In Covid-19 Patientsmentioning
confidence: 99%
“…Diabetes is a chronic metabolic disease and is characterized by insulin resistance and loss of pancreatic β-cell function [1,2]. Hyperglycemia is one of the central factors for the development of oxidative stress that induces important complications in diabetic patients [3].…”
Section: Introductionmentioning
confidence: 99%